2010
DOI: 10.1074/jbc.m109.073106
|View full text |Cite
|
Sign up to set email alerts
|

α2,6-Sialic Acid on Platelet Endothelial Cell Adhesion Molecule (PECAM) Regulates Its Homophilic Interactions and Downstream Antiapoptotic Signaling

Abstract: Antiangiogenesis therapies are now part of the standard repertoire of cancer therapies, but the mechanisms for the proliferation and survival of endothelial cells are not fully understood. Although endothelial cells are covered with a glycocalyx, little is known about how endothelial glycosylation regulates endothelial functions. Here, we show that α2,6-sialic acid is necessary for the cell-surface residency of platelet endothelial cell adhesion molecule (PECAM), a member of the immunoglobulin superfamily that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 36 publications
(38 reference statements)
3
76
0
Order By: Relevance
“…NEU1 Impairs EC Capillary-like Tube Formation-Because a number of EC sialoproteins participate in the angiogenic response (17)(18)(19)(20)(21)(22)(23) and the angiogenic phenotype is associated with altered sialylation patterns (3-6), we asked whether NEU1 might influence EC capillary-like tube formation in a Matrigel system as a measure of in vitro angiogenesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NEU1 Impairs EC Capillary-like Tube Formation-Because a number of EC sialoproteins participate in the angiogenic response (17)(18)(19)(20)(21)(22)(23) and the angiogenic phenotype is associated with altered sialylation patterns (3-6), we asked whether NEU1 might influence EC capillary-like tube formation in a Matrigel system as a measure of in vitro angiogenesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…CD31 Is an in Vivo NEU1 Substrate-CD31 participates in both EC migration (52,54) and angiogenesis (52,(55)(56)(57) and in human umbilical vein ECs (HUVECs) is sialylated via ␣2,6-linkage (20). We first asked whether in HPMECs, CD31 is similarly sialylated via ␣2,6-linkages.…”
Section: Neu1 Inhibits Ec Migration In a Woundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by our group and others have shown that ST6Gal-I-directed ␣2-6 sialylation of selected receptors serves as a key negative regulator of galectin-induced apoptosis (39,42,43). Additionally, the diminished internalization of PECAM due to ␣2-6 sialylation allows anti-apoptotic signaling from PECAM for a longer time interval (40). It has also been determined that ST6Gal-I levels are up-regulated after radiation treatment in mice (44), and these higher levels confer protection against radiation-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…5D), suggesting that adipogenesis is abnormally enhanced in these mutant mice. St6gal1 knockout mice have been reported to show multiple phenotypes involving abnormal B cell responses (61), altered T cell development in the thymus (62), and vulnerability of endothelial cells to apoptotic stimuli (63), but the effects of St6gal1 deficiency on adipogenesis have not yet been investigated. It was reported previously that SNPs at the St6gal1 gene are associated with obesity and type 2 diabetes (64,65).…”
Section: Journal Of Biological Chemistry 2281mentioning
confidence: 99%